Chatter Stability Analysis of Milling Processes. Issue 1 (8th October 2019) - Binder, Roman; Ellermann, Katrin; Sehrschön, Harald
Abstract: Full utilization of the available machine tool cutting performance is often inhibited by chatter vibrations which can lead to poor surfaces, reduced tool life, increased noise emissions and even damage to the machine tool. In this contribution, a systematic approach for modelling regenerative chatter based on measured, modal models of the machine tool is presented. Furthermore, three different methods for solving the governing equations and generating stability charts are compared.